Does sex alter the relationship between CYP2B6 variation, hydroxybupropion concentration and bupropion‐aided smoking cessation in African Americans? A moderated mediation analysis. (3rd December 2021) - Chenoweth, Meghan J.; Peng, Annie R.; Zhu, Andy Z. X.; Cox, Lisa Sanderson; Nollen, Nikki L.; Ahluwalia, Jasjit S.; Benowitz, Neal L.; Knight, Jo; Swardfager, Walter; Tyndale, Rachel F.
Abstract: Background and Aims: CYP2B6, a genetically variable enzyme, converts bupropion to its active metabolite hydroxybupropion. CYP2B6 activity and bupropion‐aided cessation differ between women and men. The aim of this study was to determine whether genetically normal (versus reduced) CYP2B6 activity increases bupropion‐aided cessation in African American smokers via higher hydroxybupropion concentration, and whether this differs by sex. Design and Setting: Secondary analysis of a smoking cessation clinical trial (NCT00666978). Participants/Cases: African American light smokers (≤ 10 cigarettes/day). Interventions: Participants were treated with bupropion for 7 weeks. Measurements: Participants with detectable bupropion and/or hydroxybupropion concentrations were divided into normal ( n = 64) and reduced ( n = 109) CYP2B6 activity groups based on the presence of decreased‐function CYP2B6*6 and CYP2B6*18 alleles. Biochemically verified smoking cessation was assessed at week 3, end of treatment (7 weeks) and follow‐up (26 weeks). Findings: Normal (versus reduced) CYP2B6 activity was associated with increased cessation at week 7, which was mediated by higher hydroxybupropion concentration [odds ratio (OR) = 1.25, 95% confidence interval (CI) = 1.03, 1.78]; this mediation effect persisted at week 26 (OR = 1.23, 95% CI = 1.02, 1.70). The mediation effect was similar in women ( n = 116; OR = 1.33, 95% CI = 1.01, 2.30) and men ( n = 57; OR = 1.33, 95% CI = 0.92, 3.87). Moreover, sex did not appear to moderate the mediation effect, although this should be tested in a larger sample. Conclusions: In African American light smokers with verified early bupropion use, genetically normal CYP2B6 activity appears to be indirectly associated with greater smoking cessation success in a relationship mediated by higher hydroxybupropion concentration. The mediating effect of higher hydroxybupropion concentration on smoking cessation persists beyond the active treatment phase and does not appear to differ by sex.